The Growth Mindset of Undergraduate Students Studying Education Programs - Kamriana S.; Soma Salim S; Nasrianty Nasrianty (Indonesian Journal of Educational Studies, 2022)
Abstract. Growth Mindset is one of the determinants of a person's success in study and career. This is because people who have a growth mindset have perseverance, like challenges, and believe that their abilities will improve if they practice persistently. This quantitative study explores the growth mindset of undergraduate students studying education programs with a descriptive analysis and compares the growth mindset of students from private and public universities with independent sample t-test analysis. There were 452 undergraduate students from various universities in South Sulawesi participating: 215 students from private universities and 237 students from public universities. The results showed that the growth mindset of undergraduate students in education programs was high, both in private and public universities. However, there is a difference between the two, where the growth mindset of undergraduate students in public universirties is higher than that in private universities.